Перспективи розвитку схемо-технічних рішень зовнішнього електропостачання тягових підстанцій залізниць - Доманський, Ілля Валерійович (НТУ "ХПІ", 2013)
On the basis of analysis of classic charts of feed of haulings ubstations of railways from grids conceptual directions of development of electric net works of external power supply of hauling substations are worked out in the conditions of market economy and normative requirements electroenergy of Ukraine, which allows to provide energy keeping their work.
Keywords: електромережі; енергосистеми; енергозбереження; схеми живлення